Własność ziemska w województwie wołyńskim w 1570 roku - Anusik, Zbigniew (Przegląd Nauk Historycznych, 2011)
There is a common and consolidated opinion among Polish historians that Volhynia was a mainstay of the political and economic influence of the great landowners. But in the literature of the subject we could not find any details concerning sizes of the estates and their mutual relations. However, at the end of the 19th century, it was published an invaluable source (the tax register of 1570) which could be a base to reconstruct a state of own of the landlords in Volhynia voivoedship in the times of Lublin Union (1569). After a detailed analysis of the mentioned source the Author is able to state that in 1570 there were 382 landowners in Volhynia voivodeship. Nine owners of the biggest estates (latifundium) paid taxes which total amount was 43,51% of all landowners’ payment. Twenty seven great landowners paid 22,80% of all taxes in voivodeship. It means that 36 of the richest landlords of Volhynia had estates in which lived 66,30% (almost 200 000 persons) of all inhabitants of the voivodeship. One hundred fifty one middle landlords paid taxes which amounted to 20,41% of all taxes. The biggest group of the landlords, 195 owners of small estates, paid only 3,02% of all taxes paid in the Volhynia voivodeship. The owners of Crown estates paid 4,66%, and clergy paid 5,61% of all taxes collected in the Volhynia voivodeship. Very interesting is also a statement that 7 of the most famous families of the princes (descendents of the old Gediminids and Rurikids dynastic families): Ostrogski, Czartoryski, Zasławski, Korecki, Wiśniowiecki, Sanguszko and Zbaraski paid 43,75% of all taxes in Volhynia and the area of their large estates was over 24 000 sq. km. It means that they were owners of 59,01% of the area of the voivodeship. After a detailed analysis of the source the Author is also able to state that in the first years after the Lublin Union Volynhia voivoedship was a well populated and rich region of the Polish Republic. This voivodeship could be a very convenient base to the expansion of local great landlords towards the near empty lands of Kiev and Bratslav voivodeships.